Implementasi Strategi Pembelajaran Aktif (Active Learning) Untuk Meningkatkan Partisipasi Siswa Dalam Pembelajaran Pendidikan Agama Islam - Elgi Septrio Neldi; Gufra Ifnaldi; Gusmaneli . (Journal Of Informatics And Busisnes, 2026)
This study aims to examine the implementation of active learning strategies as an effort to enhance student participation in Islamic Religious Education (PAI) at the senior high school level. The low level of student participation in teacher-centered PAI learning serves as the primary background of this research. A systematic literature review method was employed, analyzing primary and secondary sources including national and international journal articles, pedagogical textbooks, and research reports published between 2020 and 2025. The results indicate that the application of active learning strategies—such as Think-Pair-Share (TPS), Jigsaw, Problem-Based Learning (PBL), group discussions, simulations/role-plays, and project-based learning—significantly improves students' cognitive, affective, and psychomotor engagement. The enhancement of student participation is reflected not only in verbal classroom activity but also in intrinsic motivation, critical thinking skills, and a deeper understanding of Islamic values. The study also identifies several implementation challenges, including limited teacher pedagogical competence, insufficient learning facilities, and the need for curriculum adaptation aligned with the Merdeka Curriculum principles. The study concludes that active learning offers a concrete and workable response to the prevailing pedagogical challenges, enabling a shift in PAI learning from passive reception toward active, meaningful, and student-centered engagement.